Probiotic activity of Bacillus subtilis metabolites in experimentally induced dysbiosis in mice - S. А. Lazarev; N. O. Vartanova; A. V. Poddubikov; N. A. Mikhailova (Биопрепараты: Профилактика, диагностика, лечение, 2023)
Scientific relevance. A promising option for dysbiosis correction is the use of metabiotics, products based on metabolites of probiotic microorganisms. During fermentation, Bacillus subtilis bacteria (strains 3H and 1719) produce metabolites that exhibit probiotic properties in vitro. These observations in vitro motivate an in vivo investigation of B. subtilis metabolite effects on colonic mucosal microbiota in mice in experimentally induced dysbiosis and an assessment  of the potential of B. subtilis metabolites as metabiotics.Aim. The authors aimed to compare the probiotic activity of B. subtilis 3H and B. subtilis 1719 metabolites and a commercial metabiotic in antibiotic-induced dysbiosis in mice.Materials and methods. The authors induced experimental dysbiosis in BALB/c mice weighing 18–20 g by intraperitoneal injection of gentamicin. For subsequent correction, the test groups received sorbent-bound B. subtilis metabolites, and the comparison group received a commercial metabiotic containing B. subtilis metabolites (VKPM B-2335(3)3) via intragastric injection   for 21 days. The quantitative and qualitative analysis of colonic mucosal microbiota included microbial culturing and colony identification by MALDI-TOF mass spectrometry.Results. Antibiotic-induced colonic dysbiosis in mice manifested itself as a decrease in the dominant microbiota and an increase in opportunistic pathogens. After 7 days of metabolite administration, the Lactobacillus population returned to normal in all treatment groups. The mice that received B. subtilis 3H metabolites showed the best results: their Lactobacillus spp. composition corresponded to that of intact animals. The content of Lac+ Escherichia coli returned to 100%   in all treatment groups. After 21  days  of  metabolite  administration,  the  authors  observed the elimination of bacteria (Rodentibacter spp., Aerococcus spp.) and fungi (Trichosporon spp., Kazachstania spp.) in the B. subtilis 3H group; Trichosporon spp. (no effect on Kazachstania spp.) in the B. subtilis 1719 group; and Enterococcus spp., Kazachstania spp., and Trichosporon spp. (no effect on Rodentibacter spp. and Aerococcus spp.) in the commercial metabiotic group.Conclusions. Metabolites of B. subtilis strains 3H and 1719 help to restore the diversity and abundance of  colonic  microbiota  in  antibiotic-induced  dysbiosis.  The differences  observed in microbiota re-establishment in the treatment groups indicate that there is interstrain variability in the probiotic activity of B. subtilis metabolites.